Opportunities and Challenges of Blockchain Technology in Non-Crypto Sectors - Wu, Hwang Tsung; Huang, Tang Chen; Foley, Cotman; Stuart, Mark (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Blockchain technology has evolved into a foundational technology with transformative potential across various industries, extending beyond its initial application in cryptocurrencies. This research aims to explore the application of blockchain in logistics, healthcare, and banking sectors in California, focusing on the regulatory challenges and opportunities it presents. The primary research questions include: What are the practical applications and benefits of blockchain in these sectors? What regulatory barriers hinder its adoption? Employing a mixed-methods approach, this study combines qualitative case studies through semi-structured interviews with blockchain experts, industry practitioners, and policymakers, alongside quantitative analysis of market trends from the summer of 2023. The findings reveal that blockchain significantly enhances transparency and efficiency, with 75% of logistics participants acknowledging its benefits, a 50% adoption rate in banking, and 90% of stakeholders reporting increased transaction transparency. However, challenges remain, including fragmented regulations, high implementation costs, and scalability issues, particularly in healthcare, where adoption is low at 36%. Future research should focus on longitudinal studies to assess the long-term impacts of regulatory changes on blockchain adoption, as well as examining the effectiveness of collaborative frameworks among industry stakeholders to drive innovation. By addressing these challenges, this research contributes to the ongoing discourse on how blockchain can be effectively implemented and regulated across various sectors in the United States.